2019
DOI: 10.1111/all.13726
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated fatty acid metabolism in nasal polyp‐derived eosinophils from patients with chronic rhinosinusitis

Abstract: and Technology (PRESTO) (to M.A.), and Ono Pharmaceutical Company. AbstractBackground: Eosinophils are multifunctional granulocytes capable of releasing various cytokines, chemokines, and lipid mediators. We previously reported dysregulated fatty acid metabolism in peripheral blood-derived eosinophils from patients with severe asthma. However, functional characteristics of eosinophils present in allergic inflammatory tissues remain largely uncharacterized. Methods:We established a method for isolating CD69 hi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 45 publications
(54 reference statements)
4
39
0
Order By: Relevance
“…Moreover, recent studies have revealed that eosinophils participate in the lipid network for the production of anti-inflammatory and/or pro-resolution lipid mediators [49][50][51]. It is also indicated that eosinophils may be involved in the control of nasal allergy, but details on the mechanisms have been unclear [52]. In the present study, we demonstrated the novel function of eosinophils in the control of allergic responses.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, recent studies have revealed that eosinophils participate in the lipid network for the production of anti-inflammatory and/or pro-resolution lipid mediators [49][50][51]. It is also indicated that eosinophils may be involved in the control of nasal allergy, but details on the mechanisms have been unclear [52]. In the present study, we demonstrated the novel function of eosinophils in the control of allergic responses.…”
Section: Discussionsupporting
confidence: 51%
“…For instance, alveolar macrophages isolated from severe asthma patients show reduced LXA 4 and increased LTB 4 production 59 . Furthermore, eosinophils derived from chronic rhinosinusitis patients had a reduced biosynthesis of 12/15‐LOX‐derived mediators 60 . Finally, eosinophils derived from severe asthma patients showed a reduction in PD1 biosynthesis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Leukotriene D4 (LTD4) in particular has a strong affinity for cysteinyl leukotriene‐1 and promotes bronchial constriction, leaky vasculature and mucous production . Miyata et al noted that eosinophilic LTD4 production was significantly increased in nasal polyp tissue while 15‐LOX‐derived mediators were significantly reduced. Moreover, blood eosinophils of healthy subjects treated with eosinophil activators such as IL‐5 also produced a lipid profile similar to that of eosinophilic CRS.…”
Section: Precision Medicine In Crsmentioning
confidence: 99%